Proton Magnetic Resonance Spectroscopy in Post-Traumatic Stress Disorder—Updated Systematic Review and Meta-Analysis. (October 2022) - Swanberg, Kelley M.; Campos, Leonardo; Abdallah, Chadi G.; Juchem, Christoph
A stressor-related disorder wherein traumatic experience precipitates protracted disruptions to mood and cognition, post-traumatic stress disorder (PTSD) is associated with wide-ranging abnormalities across the body. While various methods have investigated these deviations, only proton magnetic resonance spectroscopy ( 1 H MRS) enables noninvasive measurement of small-molecule metabolites in the living human. 1 H MRS has correspondingly been employed to test hypotheses about the composition and function of multiple brain regions putatively involved in PTSD. Here we systematically review methodological considerations and reported findings, both positive and negative, of the current 1 H-MRS literature in PTSD (N = 32 studies) to communicate the brain regional metabolite alterations heretofore observed, providing random-effects model meta-analyses for those most extensively studied. Our review suggests significant PTSD-associated decreases in N-acetyl aspartate in bilateral hippocampus and anterior cingulate cortex with less evident effect in other metabolites and regions. Model heterogeneities diverged widely by analysis (I 2  < 0.01% to 90.1%) and suggested regional dependence on quantification reference (creatine or otherwise). While observed variabilities in methods and reported findings suggest that 1 H-MRS explorations of PTSD could benefit from methodological standardization, informing this standardization by quantitative assessment of the existing literature is currently hampered by its small size and limited scope.